Ultrasound-assisted polysaccharide extraction from Cercis chinensis and properites, antioxidant activity of polysaccharide - Qiang Wei; Yi-han Zhang (Ultrasonics Sonochemistry, 2023)
The purpose of the study was to improve the extraction of polysaccharide from the leaves of Cercis chinensis Bunge using ultrasound, and compare the difference between boiling and ultrasound extraction in terms of polysaccharide content, monosaccharide compounds, and evaluate how the factors affected the bioactivity. The best conditions, according to the single factor experiments and the Box-Bohnken design (BBD), were an intensity of ultrasound of 180 W, duration of extraction of 40 min, proportion of water to material of 15:1 (g/g), and a higher polysaccharide yield of 20.02 ± 0.55 (mg/g) than in boiling extraction (16.09 ± 0.82 mg/g). The antioxidative experiment suggested the polysaccharide by ultrasound exhibited higher DPPH, hydroxyl radical scavenging capacities, and reducing power at 1.2–1.4 mg/mL, which was superior to the boiling polysaccharide. Further analysis showed that the ultrasonic purified polysaccharides like Gla, N-Glu, and GluA contained more total sugar and uronic acids than the boiling method did. This may indicate that the ultrasonic isolation of the polysaccharides increase the antioxidant activity of the polysaccharides.